First report of psittacine beak and feather disease in imported budgerigar (Melopsittacus undulatus) chicks in Mexico - Sánchez-Godoy, Félix; Estrada-Arzate, Daniela; Torres-Torres, Anhet A.; Chávez-Maya, Fernando; Lima-Melo, Araceli; García-Espinosa, Gary (Brazilian Journal of Veterinary Pathology, 2020)
This case reports an outbreak of psittacine beak and feather disease in imported budgerigars (Melopsittacus undulatus) in a breeding site in Mexico. Feather abnormalities occurred in 3-month-old budgerigars and the percentage of affected birds was 40 of 100 birds (40%). The disease begins with varying degrees of bare skin on the back, the ventral region of the body, and the thoracic and pelvic regions without clinical signs or mortality offspring. Thirty-tree budgerigars were referred to the laboratory for diagnostics work-up. The hemogram showed different stages of inflammation in all studied birds, where 66% had relative erythrocytosis, leukocytosis due to heterophilia and monocytosis associated with chronic inflammation. The biochemical analysis showed mainly hypoproteinemia and hypouricemia in 5/8 and 4/9 birds, respectively. The absence of feathers with some tiny calamus of the pectoral region was the most significant feature and no other significant pathologic changes were observed. Histopathologic findings were apoptosis and a moderate amount of spherical intracytoplasmic basophilic inclusion bodies in clusters in some epithelial cells of feather follicles (12/14 sections examined) and bursa of Fabricius (8/10 sections examined). End-point PCR of bursa of Fabricius, genome sequencing and phylogenetic analysis, confirmed circovirus identification of the psittacine beak and feather disease virus species and belonging to the group 2 previously found in budgerigars. This is the first description of the psittacine beak and feather disease in budgerigars in Mexico showing the need of monitoring health status of companion and free-ranging endemic and endangered psittacine birds in Mexico in order to collaborate with the trade regulation of these bird species.